Comparison between TVDI and CWSI for drought monitoring in the Guanzhong Plain, China - Jian-jun BAI; Yuan YU; Liping Di (Journal of Integrative Agriculture, 2017)
Temperature vegetation dryness index (TVDI) and crop water stress index (CWSI) are two commonly used remote sensing-based agricultural drought indicators. This study explored the applicability of monthly moderate resolution imaging spectroradiometer (MODIS) normalized difference vegetation index (NDVI) and land surface temperature (LST) data for agricultural drought monitoring in the Guanzhong Plain, China in 2003. The data were processed using TVDI, calculated by parameterizing the relationship between the MODIS NDVI and LST data. We compared the effectiveness of TVDI against CWSI, derived from the MOD16 products, for drought monitoring. In addition, the surface soil moisture and monthly precipitation were collected and used for verification of the results. Results from the study showed that: (1) drought conditions measured by TVDI and CWSI had a number of similarities, which indicated that both CWSI and TVDI can be used for drought monitoring, although they had some discrepancies in the spatiotemporal characteristics of drought intensity of this region; and (2) both standardized precipitation index (SPI) and SM contents at the depth of 10 and 20 cm had better correlations to CWSI than to TVDI, indicating that there were more statistically significant relationships between CWSI and SPI/SM, and that CWSI is a more reliable indicator for assessing and monitoring droughts in this region.